The Nociceptin/Orphanin FQ peptide receptor antagonist, SB-612111, improves cerebral blood flow in a rat model of traumatic brain injury - Al Yacoub, Omar N.; Tarantini, Stefano; Zhang, Yong; Csiszar, Anna; Standifer, Kelly M. (Frontiers in Pharmacology, 2023)
Traumatic brain injury (TBI) affects more than 2.5 million people in the U.S. each year and is the leading cause of death and disability in children and adults ages 1 to 44. Approximately 90% of TBI cases are classified as mild but may still lead to acute detrimental effects such as impaired cerebral blood flow (CBF) that result in prolonged impacts on brain function and quality of life in up to 15% of patients. We previously reported that nociceptin/orphanin FQ (N/OFQ) peptide (NOP) receptor antagonism reversed mild blast TBI-induced vestibulomotor deficits and prevented hypoxia. To explore mechanisms by which the NOP receptor-N/OFQ pathway modulates hypoxia and other TBI sequelae, the ability of the NOP antagonist, SB-612111 (SB), to reverse TBI-induced CBF and associated injury marker changes were tested in this study.Male Wistar rats randomly received sham craniotomy or craniotomy + TBI via controlled cortical impact. Injury severity was assessed after 1 hour (modified neurological severity score;(mNSS). Changes in CBF were assessed 2 hours post-injury above the exposed cortex using laser speckle contrast imaging in response to the direct application of increasing concentrations of vehicle or SB (1, 10, and 100 µM) to the brain surface. TBI increased mNSS scores compared to baseline and confirmed mild TBI (mTBI) severity. CBF was significantly impaired on the ipsilateral side of the brain following mTBI, compared to contralateral side and to sham rats. SB dose-dependently improved CBF on the ipsilateral side after mTBI compared to SB effects on the respective ipsilateral side of sham rats but had no effect on contralateral CBF or in uninjured rats. N/OFQ levels increased in the cerebral spinal fluid (CSF) following mTBI, which correlated with the percent decrease in ipsilateral CBF. TBI also activated ERK and cofilin within 3 hours post-TBI; ERK activation correlated with increased CSF N/OFQ. In conclusion, this study reveals a significant contribution of the N/OFQ-NOP receptor system to TBI-induced dysregulation of cerebral vasculature and suggests that the NOP receptor should be considered as a potential therapeutic target for TBI.